Laminated body
By forming a laminate with specific haze values on a transparent substrate, the hydrophilic resin layer of a tetrafluoroethylene resin having a sulfonic acid group in the side chain and a binder resin are solved, and the problems of oil stain removal and hydrophilic recovery are solved. , realizes the self-cleaning function of transparent substrates and long-term hydrophilic maintenance, and is suitable for the protection of optical components such as monitors and surveillance cameras.
Patent Information
- Application Number
- CN202010120224.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-03-06
- Filing Date
- 2020-02-26
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2040-02-26
AI Technical Summary
The existing technology cannot effectively remove oil stains attached to transparent substrates by rainwater or water washing and restore their hydrophilicity, especially on transparent covers of optical components such as monitors and surveillance cameras, which are difficult to maintain and limited maintenance opportunities.
The laminated body of a hydrophilic resin layer containing a tetrafluoroethylene resin having a sulfonic acid group in the side chain and a base material is used to control the difference between the haze value and haze value of the laminated body to be less than 1%. Achieve self-cleaning function of oil stains and long-term hydrophilic recovery.
Oil stains can be easily removed by rainwater or water washing, and the hydrophilicity of the transparent substrate is maintained, reducing maintenance costs and frequency, and is suitable for protecting optical components.
Smart Images

Figure CN111660617B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a laminate having a self-cleaning function for oil stains. Background Art
[0002] Generally, as an antifouling technology, it is desired to impart hydrophilicity to a substrate so that attached dirt can be easily washed away by rainwater or water washing.
[0003] There has been proposed a technique for washing away dirt attached to the outer wall of a building by spraying rain or shower water (see, for example, Patent Document 1).
[0004] Patent Document 1 describes a coating material comprising Nafion (registered trademark), a graft polymer composed of repeating units of high molecular weight tetrafluoroethylene having perfluorosulfonic acid groups in side chains, and describes that by applying the coating material to the outer wall, the coated surface exhibits superhydrophilicity over a long period of time.
[0005] In addition, Reference Document 2 describes that a coating material including a metal oxide having a photocatalytic function and the above-mentioned Nafion (registered trademark) is applied to a steel plate and a tent base.
[0006] On the other hand, in recent years, the installation of monitors and surveillance cameras has increased both outdoors and indoors. From the perspective of reducing maintenance, it is ideal that the transparent substrate that serves as a transparent cover for protecting optical elements such as these monitors and surveillance cameras is a substrate that can easily wash away dirt attached to the transparent substrate through rainwater or water washing. In particular, the opportunity for maintenance is sometimes limited depending on the installation location of the monitors and surveillance cameras. Therefore, the transparent substrate that protects the optical element is expected to have a self-cleaning function that can wash away any dirt when water drops are washed away by rainwater or water washing. In particular, from a practical point of view, the transparent substrate that protects the optical element is expected to have a transparent substrate that has a self-cleaning function for oil stains.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2006-45370
[0010] Patent Document 2: Japanese Patent Application Publication No. 2006-233073 Summary of the invention
[0011] Problem that the invention aims to solve
[0012] However, Patent Documents 1 and 2 do not specifically describe dirt washed away by rainfall or shower water, and Patent Document 2 only describes dirt caused by rain marks in the background art section.
[0013] In the above-mentioned Patent Documents 1 and 2, there is no description as to whether the dirt can be easily washed off by rainwater or water washing and whether the hydrophilicity can be restored when oil is attached.
[0014] From the perspective of providing a transparent substrate that exhibits a self-cleaning function that allows dirt to be easily washed away by rain or water, the technologies described in Patent Documents 1 and 2 are not fully satisfactory for any dirt, including oil dirt, and there is room for improvement.
[0015] Therefore, the object of the present invention is to provide: a laminate that can be used as a transparent substrate for protecting optical elements, which has a self-cleaning function that can easily wash away oil stains through rainwater or water washing, can easily restore hydrophilicity, and can further maintain hydrophilicity stably for a long time.
[0016] Solutions for solving problems
[0017] The present inventors have conducted intensive studies to solve the above-mentioned problems and have found that a laminate having a hydrophilic resin layer containing a tetrafluoroethylene resin having a sulfonic acid group in a side chain and a binder resin and a substrate, wherein the haze value of the substrate is below a specific value and the difference between the haze value of the laminate and the haze value of the substrate is below a specific value, can solve the above-mentioned problems, thereby completing the present invention.
[0018] That is, the present invention includes the following aspects.
[0019] According to the invention described in technical solution 1,
[0020] Provided is a laminated body characterized in that it is a laminated body formed by laminating a hydrophilic resin layer and a substrate, wherein the hydrophilic resin layer contains a tetrafluoroethylene resin having a sulfonic acid group in a side chain and a binder resin,
[0021] The haze value of the substrate is 0.2% or less, and the difference between the haze value of the laminate and the haze value of the substrate is 1% or less.
[0022] Thus, the following laminate can be provided: it is a laminate that can be used as a transparent substrate to protect optical elements, has a self-cleaning function that can easily wash away oil stains and restore hydrophilicity through rainwater or water washing, and can further maintain hydrophilicity stably for a long time.
[0023] According to the invention described in technical solution 2,
[0024] There is provided a laminate according to claim 1, wherein the binder resin is at least one resin selected from the group consisting of urethane acrylic resins, vinylidene fluoride copolymers, acrylic resins, fluororesin emulsions, and self-crosslinking polyester resins.
[0025] This allows selection of a binder resin that is compatible with the tetrafluoroethylene resin having a sulfonic acid group in a side chain and easily bonds to the substrate surface, and more reliably obtains a laminate that exhibits the specific haze value defined in the present invention.
[0026] According to the invention described in technical solution 3,
[0027] Provided is a laminate as described in any one of technical solutions 1 or 2, wherein the hydrophilic resin layer contains SiO2 particles.
[0028] Thereby, the hydrophilic function of the surface of the hydrophilic resin layer can be further enhanced.
[0029] Effects of the Invention
[0030] According to the present invention, the following laminate can be provided: it is a laminate that can be used as a transparent substrate to protect optical elements, and it has a self-cleaning function that can easily wash away oil stains and restore hydrophilicity through rainwater and water washing, and can further stably maintain hydrophilicity for a long time. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a schematic cross-sectional view showing one embodiment of the layer structure of the laminate of the present invention.
[0032] Figure 2 This is a schematic cross-sectional view showing another embodiment of the layer structure of the laminate of the present invention.
[0033] Figure 3 This is a graph showing the relationship between the amount of change Δ(°) of the contact angle in Test Example 1 and the haze value of the laminate.
[0034] Figure 4 This is a graph showing the relationship between the amount of change Δ(°) of the contact angle in Test Example 1 and the haze value of the laminate.
[0035] Figure 5 This is a schematic diagram of a photoelectron spectrum obtained by analyzing the surface of Sample 5 of Test Example 1 by the XPS method (X-ray photoelectron spectroscopy).
[0036] Figure 6 This is a schematic diagram of a photoelectron spectrum obtained by analyzing the surface of Sample 9 of Test Example 1 by the XPS method (X-ray photoelectron spectroscopy).
[0037] Figure 7This is a schematic diagram of a photoelectron spectrum obtained by analyzing the surface of the sample 10 of Test Example 1 by the XPS method (X-ray photoelectron spectroscopy).
[0038] Figure 8 This is a graph showing the measurement results of the contact angle after the abrasion test in Example 6.
[0039] Fig. 9A This is a photograph of the surface of the laminate of Example 7 before the test.
[0040] Fig. 9B This is a photograph of the surface of the laminated body of Example 7 during the test.
[0041] Fig. 9C This is a photograph of the surface of the laminate of Example 7 after the test.
[0042] Fig.9D This is a photograph of the surface of the laminate of Example 7 after the test and after water was applied.
[0043] Description of Reference Numerals
[0044] 1Layer
[0045] 2Hydrophilic resin layer
[0046] 3. Substrate
[0047] 4Tetrafluoroethylene resin with sulfonic acid groups on the side chains
[0048] 5. Binder resin
[0049] 6SiO2 particles DETAILED DESCRIPTION
[0050] Hereinafter, the laminated body of the present invention will be described in detail, but the description of the technical features described below is an example as one embodiment of the present invention and is not limited to these contents.
[0051] (Laminated body)
[0052] The laminate of the present invention is obtained by laminating a hydrophilic resin layer and a substrate.
[0053] The hydrophilic resin layer contains a tetrafluoroethylene resin having a sulfonic acid group in a side chain and a binder resin.
[0054] In the laminate of the present invention, the haze value of the substrate is less than 0.2%, and the difference between the haze value of the laminate of the present invention and the haze value of the substrate (hereinafter, in this specification, "the difference between the haze value of the laminate and the haze value of the substrate" is also referred to as "the haze value involved in the hydrophilic resin layer") is less than 1%.
[0055] A schematic diagram of the layer structure of a laminated body according to one embodiment of the present invention is shown in Figure 1 .
[0056] A laminate 1 according to one embodiment of the present invention is as follows Figure 1 As shown, the hydrophilic resin layer 2 and the base material 3 are laminated. The hydrophilic resin layer 2 contains a tetrafluoroethylene resin 4 having a sulfonic acid group in a side chain and a binder resin 5.
[0057] <Hydrophilic resin layer>
[0058] The hydrophilic resin layer contains a tetrafluoroethylene resin having a sulfonic acid group in a side chain and a binder resin, and may contain other components as necessary.
[0059] 《Tetrafluoroethylene resin having sulfonic acid groups on side chains》
[0060] As the above-mentioned tetrafluoroethylene resin having a sulfonic acid group in the side chain (hereinafter, in this specification, "tetrafluoroethylene resin having a sulfonic acid group in the side chain" is also referred to as "fluorine-based ionomer resin"), for example, a tetrafluoroethylene resin obtained by graft polymerization of perfluorosulfonic acid as described in the above-mentioned Patent Document 1 (Japanese Patent Publication No. 2006-45370) can be used.
[0061] Specifically, for example, a tetrafluoroethylene resin obtained by graft-polymerizing a perfluorosulfonic acid having a sulfonic acid group at a terminal represented by the following formula (1) may be mentioned.
[0062]
[0063] In the above formula (1), Rf is a perfluoroalkyl group, SO3H is a sulfonic acid group, and x and y are integers.
[0064] Examples of the perfluoroalkyl group for Rf include linear or branched perfluoroalkyl groups having a carbon number of 1 to 6. A part of the carbon atoms in the perfluoroalkyl group may be substituted with oxygen atoms.
[0065] Preferred examples of the perfluoroalkyl group for Rf include perfluoroalkyl groups represented by the following formula (2), formula (3) or formula (4).
[0066]
[0067] -CF2CF2- (3)
[0068] -CF2CF2CF2CF2- (4)
[0069] The content of the fluorine-based ionomer resin in the hydrophilic resin layer is not particularly limited as long as a laminate having the specific haze value defined in the present invention can be formed, and can be appropriately selected depending on the purpose. For example, it is preferably 8 to 30%, more preferably 10 to 30%, and further preferably 10 to 25%.
[0070] Binder resin
[0071] As the binder resin constituting the hydrophilic resin layer, there is no particular limitation on the type of binder resin as long as it can form a laminated body that embodies the specific haze value defined in the present invention, and it can be appropriately selected according to the purpose. From the viewpoint of reducing the haze value of the hydrophilic resin layer and the viewpoint of durability / abrasion resistance, the following resins are preferred.
[0072] The binder resin is preferably compatible with the fluorine-based ionomer resin (when the hydrophilic resin layer further contains other components described below, the compatibility with the other components is also preferably good) and easily bonded to the substrate surface.
[0073] Therefore, as the binder resin of the present invention, for example, preferably at least one resin selected from the group consisting of urethane acrylic resin, vinylidene fluoride copolymer, acrylic resin, fluororesin emulsion, and self-crosslinking polyester resin can be cited.
[0074] The urethane acrylic resin, vinylidene fluoride copolymer, acrylic resin, fluororesin emulsion, and self-crosslinking polyester resin may be used alone or in combination of a plurality of resins selected from these resins. For example, as the binder resin, a mixture of a fluororesin emulsion and a self-crosslinking polyester resin may be used.
[0075] When the binder resin of the present invention is any of these resins, the haze value of the hydrophilic resin layer and the haze value of the laminate can be reduced, and a laminate having a desired haze value can be obtained more reliably.
[0076] Among them, as the binder resin, urethane acrylic resin is more preferred.
[0077] 《Other ingredients》
[0078] The hydrophilic resin layer of the present invention may contain various particles of photocatalysts such as silicon dioxide (SiO2) and titanium oxide as needed, in addition to the fluorine-based ionomer resin and the binder resin.
[0079] In the present invention, it is preferred that the hydrophilic resin layer contains nanoparticles of SiO 2. By containing SiO 2 particles, the hydrophilicity of the surface of the hydrophilic resin layer can be further improved.
[0080] A schematic diagram of the layer structure of the laminate of the present invention when the hydrophilic resin layer contains SiO2 particles is shown in Figure 2 .
[0081] When the hydrophilic resin layer contains SiO2 particles, the laminate 1 of the present invention is as follows: Figure 2 As shown, the hydrophilic resin layer 2 contains SiO 2 particles 6 . Figure 2 In, with Figure 1 The same components are denoted by the same symbols.
[0082] The particle size and content of SiO 2 particles contained in the hydrophilic resin layer are not particularly limited as long as a laminate having the specific haze value defined in the present invention can be formed, and can be appropriately selected.
[0083] As the particle size of SiO2 particles, for example, from the viewpoint of preventing the scattering of light, preferably below 80nm, more preferably below 50nm, further preferably below 15nm. In addition, for example, from the viewpoint of preventing the aggregation of particles, preferably above 5nm, more preferably above 10nm.
[0084] The content of SiO2 particles in the hydrophilic resin layer is preferably 50% by mass or less, for example, from the viewpoint of preventing light scattering, and preferably 10% by mass or more, for example, from the viewpoint of ensuring the effect.
[0085] In the present invention, it is more preferable that the hydrophilic resin layer does not contain a photocatalyst such as titanium oxide. This is because when no photocatalyst is contained, a laminate having higher transparency can be obtained, and a laminate satisfying the characteristic of a haze value of 1% or less can be produced more reliably.
[0086] Furthermore, when the photocatalytic reaction produced by a photocatalyst such as titanium oxide is generally used to decompose oil stains and achieve an antifouling effect, there is a limitation that a sufficient antifouling effect cannot be expected in areas that are not easily exposed to light. However, in the case of a solution in which the hydrophilic resin layer does not contain a photocatalyst, since there is no need to worry about the light source, the area in which the laminate can be used can be expanded.
[0087] 《Method for forming a hydrophilic resin layer》
[0088] When the fluorine-based ionomer resin, the binder resin, and other components are contained, the other components are mixed to prepare a resin composition (coating material).
[0089] The coating material may contain a solvent as appropriate.
[0090] The solvent is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include organic solvents and mixtures of organic solvents and water. Examples of the organic solvent include methanol, ethanol, isopropanol, ethylene glycol, propylene glycol monomethyl ether, dipropylene glycol n-butyl ether, 2-butoxyethanol, methoxypropanol, methyl ethyl ketone, acetone, ethyl acetate, butyl acetate, toluene, dimethylformamide, acetonitrile, methyl isobutyl ketone, and the like.
[0091] The hydrophilic resin layer can be formed by applying the coating material on the substrate and drying the coated layer.
[0092] When the coating material contains an organic solvent, it is preferred to dry the coating layer by heating the coating layer to evaporate the organic solvent in the coating material.
[0093] The coating method is not particularly limited and may be appropriately selected depending on the intended purpose. Examples thereof include solution coating methods such as dip coating, spin coating, spray coating, roll coating, and bar coating.
[0094] The conditions for heating and drying the coating layer are not particularly limited and can be appropriately selected. For example, the conditions include heating and drying at 80 to 130° C. for 5 to 30 minutes.
[0095] As a more specific method for forming a hydrophilic resin layer, for example, the following method can be cited: using a rod coater, a coating material containing a fluorine-based ionomer resin and a binder resin is applied to a substrate, and the coating layer is heated at 120° C. for 20 minutes and dried to form a hydrophilic resin layer.
[0096] 《Thickness of hydrophilic resin layer》
[0097] The thickness of the hydrophilic resin layer is not particularly limited as long as it can form a laminate that embodies the specific haze value specified in the present invention, and can be appropriately selected. If the thickness is thick, the haze value becomes higher. Therefore, in order to make the haze value involved in the hydrophilic resin layer specified in the present invention less than 1%, it is preferred that the hydrophilic resin layer has a thinner thickness.
[0098] In addition, if the coating material is too thick when applied depending on the viscosity of the coating material, it is easy to cause problems due to sagging. Therefore, the thickness of the hydrophilic resin layer is preferably set so that the film thickness when dried is 5 μm or less.
[0099] On the other hand, it is considered that since the fluorine-based ionomer resin aggregates in a colloid state in a solvent, if the thickness of the hydrophilic resin layer is too thin, it is difficult to obtain a smooth surface.
[0100] In addition, when the hydrophilic resin layer contains SiO 2 particles, the SiO 2 particles may also form secondary particles by aggregation. Therefore, the film thickness of the hydrophilic resin layer is preferably 100 nm or more.
[0101] From the above, the thickness of the hydrophilic resin layer is preferably 100 nm to 5 μm, more preferably 2 to 5 μm, and further preferably 3 to 5 μm.
[0102] <Base material>
[0103] As the substrate constituting the laminate of the present invention, a substrate having a haze value of 0.2% or less is used.
[0104] The substrate may be any substrate as long as it can form a laminate that exhibits the specific haze value defined in the present invention. The substrate may be of any type and may be appropriately selected depending on the intended purpose.
[0105] Since the hydrophilic resin layer is composed of a resin, it is preferred that the substrate also be composed of a resin from the viewpoint of adhesion.
[0106] Generally, if a substrate with low smoothness is used, the haze value of the laminate tends to be higher. Therefore, for example, in order to obtain a laminate having a desired haze value as defined in the present invention, the substrate is preferably selected from resins such as polycarbonate resin, polyacrylic resin, polyolefin resin, cyclic olefin resin, polyester resin, etc. Among them, acrylic resin is more preferably used as the substrate from the viewpoint of transparency and cost, and polycarbonate resin is more preferably used as the substrate from the viewpoint of strength and cost.
[0107] The shape of the substrate is not particularly limited and can be appropriately selected according to the purpose. For example, the substrate may have a flat plate, sheet, film, or three-dimensional shape in the entire surface or in a portion, or may have a curvature in the entire surface or in a portion, etc., in any shape that suits the purpose.
[0108] In addition, when the substrate is formed into a film, as a molding method, for example, extrusion, casting, T-die, cutting, inflation, etc. can be cited. These films can be used as a substrate in a single layer or a plastic molding formed by multi-layer film formation can be used as a substrate.
[0109] In addition, the thickness of the substrate is not particularly limited and can be appropriately selected according to the purpose.
[0110] The haze value of the substrate is 0.2% or less as described above, but from the viewpoint of reliably forming a laminate having a specific haze value defined in the present invention, the haze value of the substrate is preferably 0.15% or less, more preferably 0.13% or less.
[0111] In order to improve the coating property of the hydrophilic resin layer or improve the adhesion to the hydrophilic resin layer, the surface of the substrate may be subjected to various surface treatments, such as ozone treatment, plasma treatment, corona treatment, silane coupling treatment, and the like.
[0112] The type of the substrate is preferably a resin, and for example, if a silane coupling agent is used as the base layer, a glass substrate may also be used.
[0113] <Haze value(%)>
[0114] The difference between the haze value of the laminate of the present invention and the haze value of the substrate (the haze value related to the hydrophilic resin layer) is 1% or less.
[0115] Furthermore, the haze value of the laminate of the present invention is more preferably 1% or less.
[0116] The haze value (the degree of fogging) is an index showing the degree of transparency, and is a value obtained by calculating the ratio of scattered light to total transmitted light.
[0117] The haze value can be measured using illuminant C in accordance with JIS K7136.
[0118] In the above-mentioned fluorine-based ionomer resin constituting the hydrophilic resin layer, the sulfonic acid (-SO3H) part of the side chain is bonded to the carbon element bonded to the fluorine element with high electronegativity. Therefore, the sulfonic acid is also easily converted into -SO3H by the interaction with the large electron-withdrawing property of the fluorine element. - H + The sulfonic acid portion of the side chain is strongly ionized, so that water molecules with high polarity are easily introduced. In the above-mentioned fluorine-based ionomer resin, the sulfonic acid portion of the side chain exhibits hydrophilicity.
[0119] On the other hand, tetrafluoroethylene resin itself exhibits hydrophobicity. Therefore, tetrafluoroethylene resin having a sulfonic acid group in the side chain has both hydrophobicity and hydrophilicity. For example, when measuring static wettability, the influence of the Teflon skeleton is high, and hydrophobicity is exhibited, but the droplets are large, or when measuring dynamic wettability such as making the droplets fall, hydrophilicity is exhibited under the influence of -SO3H that exists partially.
[0120] Therefore, it exhibits behavior different from that of general hydrophilic surfaces.
[0121] Therefore, the present inventors studied oil stains and found that oil stains attached to the surface of a hydrophilic resin cannot be washed away even by wiping in running water and that the hydrophilicity may not be restored, which affects the haze value.
[0122] The inventors of the present invention have further studied the haze value involved in the hydrophilic resin layer and the haze value of the laminate, and found that in order to remove oil stains and restore hydrophilicity, regardless of the surface composition of the hydrophilic resin layer, it depends on the haze value of the laminate, and if the difference between the haze value of the laminate and the haze value of the substrate (the haze value involved in the hydrophilic resin layer) is less than 1%, the hydrophilicity can be easily restored and maintained for oil stains.
[0123] The meaning of the haze value defined in the present invention is explained according to Test Examples 1 and 2 described below.
[0124] [Test Example 1]
[0125] A hydrophilic resin layer containing a tetrafluoroethylene resin having a sulfonic acid group in a side chain and a binder resin is formed on a substrate.
[0126] As shown in Table 1 below, samples 1 to 11 were prepared having different compositions of the hydrophilic resin layer.
[0127] In Table 1, the tetrafluoroethylene resin (fluorine-based ionomer resin) having a sulfonic acid group in a side chain is a fluorine-based ionomer resin (manufactured by Daikin Industries, Ltd.) having the formula (3) as Rf of the formula (1).
[0128] In sample 1, the hydrophilic resin layer contained 10 mass % of a fluorine-based ionomer resin (the contents of the fluorine-based ionomer resin in other samples are shown in Table 1).
[0129] In Sample 1, a fluororesin emulsion (manufactured by Daikin Industries, Ltd.) was used as a binder resin (the same fluororesin emulsion as that of Sample 1 was also used in the other Samples 2 to 8).
[0130] In sample 2, the hydrophilic resin layer contains 30 mass % of SiO 2 particles (the contents of SiO 2 particles or TiO 2 particles in other samples are shown in Table 1).
[0131] As SiO2 particles in each sample, Silicasol IPA-ST-L (particle size: 40 to 50 nm) manufactured by Nissan Chemical Industries, Ltd. was used in Samples 2 to 5, and Silicasol IPA-ST (particle size: 12 nm) manufactured by Nissan Chemical Industries, Ltd. was used in Sample 9.
[0132] As TiO 2 particles in each sample, those manufactured by Ishihara Sangyo Co., Ltd. (particle size: 5 to 15 nm) were used.
[0133] In Sample 9, a urethane acrylic resin (manufactured by DSM Co., Ltd.) was used as a binder resin (in the other Sample 10, the same urethane acrylic resin as that of Sample 9 was also used).
[0134] In Sample 11, a mixture of a fluororesin emulsion (manufactured by Daikin Industries, Ltd.) and a self-crosslinking polyester resin (manufactured by Unitika Ltd.) was used as a binder resin.
[0135] The substrate used was a polycarbonate substrate (ECW100t=3 (thickness 3 mm), 10 cm square, manufactured by Sumitomo Bakelite Co., Ltd.) The haze value of the polycarbonate substrate was 0.13%.
[0136] The coating material was prepared by mixing the components constituting the hydrophilic resin layer at the ratio shown in Table 1 and further mixing a solvent.
[0137] In Samples 1 to 8, isopropyl alcohol, 2-butoxyethanol, and water were used as the solvent.
[0138] In samples 9 and 10, isopropyl alcohol and water were used as solvents.
[0139] In Sample 11, isopropyl alcohol, water, and dipropylene glycol n-butyl ether were used as solvents.
[0140] The coating material was applied onto a polycarbonate substrate using a bar coater #10 and dried at 120° C. for 20 minutes to obtain a laminate having a hydrophilic resin layer laminated on the substrate.
[0141] The film thickness of the hydrophilic resin layer before drying was 20 μm, and the film thickness after drying was 5 μm.
[0142] For each sample, gear oil was dropped onto the surface of the hydrophilic resin layer, and the layer was left to stand for 1 hour, and then the layer was washed with water while being gently wiped with a Bemcot.
[0143] The contact angle (°) before the gear oil was dripped and the contact angle (°) after the gear oil was washed (cleaned) were measured for the surface of the hydrophilic resin layer in the laminate of each sample. Then, the change Δ (°) between the contact angle before the gear oil was dripped and the contact angle after washing was calculated.
[0144] Here, the contact angle (°) is as follows: a 10 μL water droplet is dropped on the sample surface from a height of 10 cm, and the angle between the water droplet formed on the sample and the sample surface is measured using FAMAS, a multifunctional comprehensive analysis software installed in a contact angle meter manufactured by Kyowa Interface Science Co., Ltd.
[0145] The constituent components and content of the hydrophilic resin layer in each sample are shown in the following Table 1. In addition, the haze value (%) of the laminate, the contact angle (°) before dropping the gear oil on the laminate, the contact angle (°) after washing, and the change in the contact angle Δ (°) are shown in the following Table 1.
[0146] Furthermore, the relationship between the change Δ(°) between the contact angle before adding the gear oil and the contact angle after washing and the haze value of the laminate is shown in FIG. Figure 3 and Figure 4 .
[0147] [Table 1]
[0148]
[0149] According to Table 1, Figure 3 and Figure 4 The results show that the degree of recovery of the hydrophilicity of the laminate to oil stains is different depending on whether the haze value defined in the present invention is 1% or less. It shows that for a laminate whose contact angle before adding gear oil and the contact angle after cleaning have a change Δ(°) of 20 or less, and more preferably 10 or less, the oil stains can be easily washed away by rainwater or water washing. Therefore, in order to obtain a laminate that can easily wash away oil stains by rainwater or water washing, can easily restore hydrophilicity, and can further stably maintain hydrophilicity for a long time, the laminate must have a substrate with a haze value of less than 0.2%, and the difference between the haze value of the laminate and the haze value of the substrate (the haze value involved in the hydrophilic resin layer) is 1% or less.
[0150] The present inventors have confirmed that in order to obtain a laminate that satisfies the self-cleaning function for oil stains, it is important to reduce the haze value and obtain a laminate that has a haze value below the specified value specified in the present invention, that is, a haze value of 1% or less involving the hydrophilic resin layer.
[0151] like Figure 3 and 4 As shown in , the self-cleaning effect on oil stains is correlated with the haze value of the laminate. On the other hand, the present inventors have confirmed that the self-cleaning effect on oil stains does not depend on the components constituting the hydrophilic resin layer or the surface composition of the hydrophilic resin layer.
[0152] Therefore, according to the following Test Example 2, it is shown that the self-cleaning effect on oil stains does not depend on the components constituting the hydrophilic resin layer or the surface composition of the hydrophilic resin layer.
[0153] [Test Example 2]
[0154] Using samples 5, 9 and 10 prepared in the above-mentioned Test Example 1, the surface compositions of these samples were analyzed.
[0155] Each sample was cut into pieces of about 1×2 cm using an ultrasonic cutter, and the types of elements present on the outermost surface (~10 nm) were analyzed by the XPS method (X-ray Photoelectron Spectroscopy).
[0156] The schematic diagrams of the photoelectron spectra obtained by analyzing the surfaces of samples 5, 9, and 10 of Test Example 1 by the XPS method (X-ray photoelectron spectroscopy) are shown in FIG. Figures 5 to 7 In addition, the compositions of the outermost surfaces of Samples 5, 9, and 10 of Test Example 1 are collectively shown in Table 2 below.
[0157] [Table 2]
[0158] element C O F S Si N Sample 5 31.21 30.62 22.04 1.06 13.36 1.71 Sample 9 31.43 29.93 23.86 0.91 12.70 1.17 Sample 10 67.02 15.37 14.79 0.55 - 2.29
[0159] The results in Tables 1 and 2 show that, although the constituent components forming the hydrophilic resin layer are different for samples 5 and 9, the types and ratios of the elements on the outermost surface of the hydrophilic resin layer show substantially the same results. On the other hand, the surface composition of the hydrophilic resin layer of sample 10 is significantly different from that of the other samples 5 and 9.
[0160] As shown in the results of Table 1, regarding the self-cleaning effect, the self-cleaning effect was confirmed in Samples 9 and 10, but the self-cleaning effect was not confirmed in Sample 5.
[0161] That is, it can be seen from the results of Tables 1 and 2 that the self-cleaning effect is strongly affected by the haze value caused by the surface composition of the hydrophilic resin layer. It can also be confirmed that even if the surface composition of the hydrophilic resin layer is different, as long as the laminate has a haze value of 1% or less as defined in the present invention, the laminate can exhibit a self-cleaning effect.
[0162] Thus, a laminate having a haze value of 1% or less in the hydrophilic resin layer exhibits a self-cleaning function that allows the oil to be easily removed by rain or water washing and the hydrophilicity to be easily restored even if oil is attached.
[0163] The mechanism by which the hydrophilicity of a laminated body having a hydrophilic resin layer and a substrate can be easily restored to oil stains by forming the laminated body having a haze value of 1% or less in the hydrophilic resin layer is not yet clear, but the present inventors consider the following.
[0164] It is speculated that for surfaces with high haze values (low smoothness), when oil adheres to micropores dominated by hydrophobicity, it is not easily affected by water washing, while for surfaces with low haze values (high smoothness), the oil is not physically restricted and is therefore washed away by water washing.
[0165] In order to obtain the laminated body embodying the desired haze value, about the hydrophilic resin layer, the kind of binder resin, the content of fluorine-based ionomer, the thickness of the hydrophilic resin layer, etc. can be considered. In the case of particles containing SiO2, it is also possible to consider the particle diameter and content of SiO2 particles without producing the aggregation of SiO2 particles. In addition, in the hydrophilic resin layer, the binder resin that the composition of the binder resin itself does not aggregate and the binder resin that has good compatibility with the fluorine-based ionomer and good adhesion with the base material can be selected. In addition, in order not to make SiO2 particles aggregate, the binder resin that the compatibility of the particles is also good can be selected with SiO2.
[0166] By taking the above-mentioned factors into consideration, the influence of the light scattering component in the hydrophilic resin layer on the haze value can be reduced, and a smooth hydrophilic resin layer with less surface irregularities can be obtained.
[0167] In addition, if there are irregularities on the surface of the substrate, the surface of the hydrophilic resin layer is also affected, so a substrate with a smooth surface with few irregularities can be used. Furthermore, the influence of the light scattering components in the substrate on the haze value can be reduced by considering the constituent components of the substrate, its type, the film thickness of the substrate, etc.
[0168] In order to obtain a laminate having a desired haze value, the above-mentioned factors can be taken into consideration.
[0169] <Application of laminated body>
[0170] As shown in the above test examples and the following embodiments, the laminate of the present invention has a self-cleaning function that can easily wash away oil stains and restore hydrophilicity by washing with water. Therefore, in an environment where oil and oil mist are attached, oil stains can be easily removed by rain or washing with water.
[0171] In addition, as shown in the following examples, the laminate of the present invention has the following effect: sand and dust are not easily attached, and even if attached, they can be easily removed by washing with water. This is considered to be because, as described above, the high ionization of the fluorine-based ionomer can obtain an antistatic function, thereby forming a surface that is not easily attached to sand and dust.
[0172] Therefore, the laminate of the present invention can be used as a transparent protective substrate with high barrier properties against sand, dust and oil stains for products in various fields such as optical parts and design parts, for example, it can be used as a transparent cover for protecting optical elements such as monitors and surveillance cameras.
[0173] Example
[0174] Hereinafter, the present invention will be described in more detail with reference to examples, but the protection scope of the present invention is not limited to these examples.
[0175] (Example 1)
[0176] A laminate is formed in which a hydrophilic resin layer is laminated on a substrate, wherein the hydrophilic resin layer contains a tetrafluoroethylene resin (fluorine-based ionomer resin) having a sulfonic acid group in a side chain, a urethane acrylic resin, and SiO2 particles.
[0177] The fluorine-based ionomer resin used was a resin having the formula (3) as Rf of the formula (1) (manufactured by Daikin Industries, Ltd.).
[0178] The urethane acrylic resin used was manufactured by DSM Corporation.
[0179] As the SiO2 particles used, Silica sol IPA-ST (particle size: 12 nm) manufactured by Nissan Chemical Industries, Ltd. was used.
[0180] The content of the fluorine-based ionomer resin in the hydrophilic resin layer was set to 25% by mass.
[0181] The content of SiO 2 particles in the hydrophilic resin layer was set to 40% by mass.
[0182] The substrate used was a polycarbonate substrate (ECW100t=3 (thickness 3 mm), 10 cm square, manufactured by Sumitomo Bakelite Co., Ltd.) The haze value of the polycarbonate substrate was 0.13.
[0183] 15 parts by mass of a fluorine-based ionomer resin, 14 parts by mass of a urethane acrylic resin, 20 parts by mass of SiO 2 particles, and 45 parts by mass of a mixed solvent of isopropyl alcohol and water were uniformly mixed to prepare a coating material.
[0184] The coating material was applied onto a polycarbonate substrate using a bar coater #10 and dried at 120° C. for 20 minutes to obtain a laminate having a hydrophilic resin layer laminated on the substrate.
[0185] The film thickness of the hydrophilic resin layer before drying was 20 μm, and the film thickness after drying was 5 μm.
[0186] Gear oil was dropped onto the surface of the hydrophilic resin layer and allowed to stand for 1 hour, and then the layer was washed with water while being gently wiped with Bemcot.
[0187] The contact angle (°) before the gear oil was dripped on the surface of the hydrophilic resin layer of the laminate and the contact angle (°) after the gear oil was washed with water (after cleaning) were measured. Then, the change Δ (°) between the contact angle before the gear oil was dripped and the contact angle after cleaning was calculated.
[0188] Here, the contact angle (°) is as follows: a 10 μL water droplet is dripped onto the surface of the hydrophilic resin layer in the laminate from a height of 10 cm, and the angle between the water droplet formed on the hydrophilic resin layer and the surface of the hydrophilic resin layer is measured using FAMAS, a multifunctional comprehensive analysis software installed in a contact angle meter manufactured by Kyowa Interface Science Co., Ltd.
[0189] (Example 2)
[0190] In Example 1, a laminate of Example 2 was prepared in the same manner as in Example 1 except that the coating material was applied to the polycarbonate substrate using a bar coater #10 and the drying conditions for drying the coating material were changed to drying at 120°C for 10 minutes.
[0191] For the laminate of Example 2, in the same manner as in Example 1, the contact angle (°) before the gear oil was dropped during the preparation of the laminate and the contact angle (°) after the gear oil was washed with water (after cleaning) were measured.
[0192] (Example 3)
[0193] A laminate of Example 3 was produced in the same manner as in Example 1 except that SiO 2 particles were not contained.
[0194] For the laminate of Example 3, the contact angle (°) before the gear oil was dropped and the contact angle (°) after the gear oil was washed with water (after cleaning) were measured in the same manner as in Example 1.
[0195] (Comparative Example 1)
[0196] In Example 1, the type of binder resin was changed to a fluororesin emulsion, the content of the fluorine-based ionomer was changed to 10% by mass, and the content of SiO2 particles (Silica sol IPA-STL (particle size: 45 nm) manufactured by Nissan Chemical Industries, Ltd.) was changed to 30% by mass. Except for this, the laminate of Comparative Example 1 was prepared in the same manner as in Example 1.
[0197] In Comparative Example 1, the fluororesin emulsion used was manufactured by Daikin Industries, Ltd.
[0198] For the laminate of Comparative Example 1, the contact angle (°) before the gear oil was dropped and the contact angle (°) after the gear oil was washed with water (after cleaning) were measured in the same manner as in Example 1.
[0199] (Comparative Example 2)
[0200] A laminate of Comparative Example 2 was produced in the same manner as in Comparative Example 1 except that SiO 2 particles were not contained.
[0201] For the laminate of Comparative Example 2, the contact angle (°) before the gear oil was dropped and the contact angle (°) after the gear oil was washed with water (after cleaning) were measured in the same manner as in Example 1 when the laminate was prepared.
[0202] The haze value (%) of the laminate, the contact angle (°) before dropping gear oil on the laminate and the contact angle (°) after washing, and the change Δ (°) of the contact angle in Examples 1 to 3 and Comparative Examples 1 to 2 are shown in Table 3 below.
[0203] [Table 3]
[0204]
[0205] (Example 4)
[0206] The laminate produced in Example 1 was stored for 1 year in a container placed in a room where temperature and humidity were not controlled.
[0207] The following experiment was conducted on the laminate of Example 1 after one year had passed.
[0208] First, the contact angle (°) of the laminate of Example 1 after one year had passed when it was taken out from the container was measured.
[0209] Next, the laminate of Example 1 after one year was washed with water, and gear oil was dripped on the surface of the hydrophilic resin layer, and after standing for one hour, it was washed with water while being gently wiped with Bemcot. The part where the gear oil was dripped was the same part as the part marked at the part where the gear oil was dripped in the experiment of dripping the gear oil one year ago.
[0210] Then, for the surface of the hydrophilic resin layer in the laminate after one year, the contact angle (°) before the addition of gear oil after water washing and the contact angle (°) after the gear oil water washing (after cleaning) were measured. Then, the change Δ(°) between the contact angle before the addition of gear oil and the contact angle after cleaning was calculated. Furthermore, the change Δ(°) between the contact angle (°) before the addition of gear oil when preparing the laminate in the experiment conducted one year ago (the contact angle of the initial value) and the contact angle after the gear oil in the laminate after one year in the experiment conducted one year later were calculated.
[0211] (Example 5)
[0212] The laminate produced in Example 2 was stored in the same container as the laminate of Example 1 used in Example 4 for 1 year.
[0213] For the laminate of Example 2 after 1 year, the contact angle (°) before adding the gear oil after washing with water and the contact angle (°) after washing with the gear oil (after cleaning) were measured by the same method as in Example 4.
[0214] (Comparative Example 3)
[0215] The laminate produced in Comparative Example 1 was stored in the same container as the laminate of Example 1 used in Example 4 for 1 year.
[0216] For the laminate of Comparative Example 1 after 1 year, the contact angle (°) before adding the gear oil after washing with water and the contact angle (°) after washing with the gear oil (after cleaning) were measured by the same method as in Example 4.
[0217] (Comparative Example 4)
[0218] The laminate produced in Comparative Example 2 was stored in the same container as the laminate of Example 1 used in Example 4 for 1 year.
[0219] For the laminate of Comparative Example 1 after 1 year, the contact angle (°) before adding the gear oil after washing with water and the contact angle (°) after washing with the gear oil (after cleaning) were measured by the same method as in Example 4.
[0220] The contact angle (°) when taken out from the container after one year, the contact angle (°) after water washing (= before adding gear oil), the contact angle (°) after water washing (after cleaning) of the gear oil, the change in contact angle Δ(°), and the change in contact angle Δ(°) from the initial value at the time of preparation in Examples 4 to 5 and Comparative Examples 3 to 4 are shown in the following Table 4.
[0221] Table 4 also lists the results listed in Table 3, including the contact angle (°) before adding gear oil, the contact angle (°) after cleaning with gear oil, and the amount of change Δ (°) in the contact angle when the laminate was produced one year ago.
[0222] [Table 4]
[0223]
[0224] (Example 6)
[0225] By the same method as in Example 1, a laminated body of Example 6 was produced.
[0226] The laminate of Example 6 was subjected to an abrasion test under the following test conditions, and then the contact angle (°) was measured in the same manner as in Example 1.
[0227] <Abrasion test conditions>
[0228] Testing machine: (Reciprocating wear testing machine (Traverse wear testing machine))
[0229] Test conditions: flannel, load 500g / 4cm 2 , reciprocating wear times 500, 1000, 1500, 2000, 2500
[0230] The measurement results of the contact angle (°) when the number of abrasions was 500, 1000, 1500, 2000, and 2500 are shown in FIG. Figure 8 .
[0231] (Example 7)
[0232] A laminate of Example 7 was prepared in the same manner as in Example 1 except that the substrate was a dome-shaped polycarbonate substrate and the method of applying the coating material on the substrate was spray coating.
[0233] Regarding the laminate of Example 7, 11 kinds of JIS test powder 1 (Kanto loam layer) were sprinkled on the dome cap. Then, the dome cap was turned over to remove sand. Furthermore, water was sprayed onto the entire dome cap to perform water cleaning.
[0234] The laminate of Example 7 is shown in the following figure, respectively, with respect to the surface before sand was sprinkled (before the test). Fig. 9A The photographs obtained by photographing the surface in the test with sand sprinkled on it are shown in Fig. 9B The photograph of the surface after the test in which the dome cover was turned over to remove the sand is shown in Fig. 9C , and then the photograph obtained by taking the surface after washing with blowing water is shown in Fig.9D .
[0235] As shown in the Examples, it is understood that the laminate of the present invention exhibits a self-cleaning function that allows oil stains to be easily washed off by water and allows hydrophilicity to be easily restored, and further, can maintain hydrophilicity stably for a long period of time.
[0236] In addition, if Figure 8 As shown in , it can be seen that the laminate of the present invention exhibits a stable contact angle value and excellent wear resistance when the number of reciprocating wear is up to 2500. Thus, the laminate of the present invention has excellent wear resistance and excellent adhesion between the substrate and the hydrophilic resin layer.
[0237] In addition, if Fig. 9A As shown in Figures 1 to 4D, it is understood that dust does not easily adhere to the laminate of the present invention, and even if dust adheres, it can be easily removed by washing with water.
Claims
1. A laminate, characterized in that: The present invention is a laminated body formed by laminating a hydrophilic resin layer and a substrate, wherein the hydrophilic resin layer contains a tetrafluoroethylene resin having a sulfonic acid group in a side chain and a binder resin. The binder resin is a urethane acrylic resin, The haze value of the substrate is 0.2% or less, and the difference between the haze value of the laminate and the haze value of the substrate is 1% or less.
2. The laminate according to claim 1, wherein The hydrophilic resin layer contains SiO2 particles.
Citation Information
Patent Citations
Super hydrophilic coating composition and coating and super hydrophilic colored steel plate
JP2006045370A
Photocatalytic coating, and steel plate and tent cloth each coated with the same
JP2006233073A
Coating material and layered body
US20120295117A1